Staphylococcal response to oxidative stress - Gaupp, Rosmarie; Ledala, Nagender; Somerville, Greg A. (Frontiers in Cellular and Infection Microbiology, 2012)
Staphylococci are a versatile genus of bacteria that are capable of causing acute and chronic infections in diverse host species. The success of staphylococci as pathogens is due in part to their ability to mitigate endogenous and exogenous oxidative and nitrosative stress. Endogenous oxidative stress is a consequence of life in an aerobic environment; whereas, exogenous oxidative and nitrosative stress are often due to the bacteria's interaction with host immune systems. To overcome the deleterious effects of oxidative and nitrosative stress, staphylococci have evolved protection, detoxification, and repair mechanisms that are controlled by a network of regulators. In this review, we summarize the cellular targets of oxidative stress, the mechanisms by which staphylococci sense oxidative stress and damage, oxidative stress protection and repair mechanisms, and regulation of the oxidative stress response. When possible, special attention is given to how the oxidative stress defense mechanisms help staphylococci control oxidative stress in the host.